KAZAKHSTAN LEGISLATION IN THE RELIGIOUS SPHERE: HISTORY AND PROSPECTS FOR DEVELOPMENT - Ongarbayev Ye.A.; Galiakbarova G.G. (Academic Journal of Physical and Chemical Sciences, 2020)
Objective: to study Kazakhstani legislation in the religious sphere in the historical aspect of development, as well as to identify and justify ways of further improvement, including through a comparative analysis with foreign legislation. Method or methodology of work: When writing a scientific article, general scientific (logical, structural and system analysis, synthesis, comparison, abstraction, induction and deduction, modeling), special techniques, methods of researching phenomena and processes (specifically historical, dialectical, formal logical, structural-functional, comparative law method) were used. The analysis of regulatory legal acts was done. Results of work: Analysis of previous regulatory legal acts, as well as the current Kazakhstan legislation in the religious sphere, the study of international experience, justification for the adoption of the draft Law of the Republic of Kazakhstan “On Amendments and Additions to Some Legislative Acts of the Republic of Kazakhstan on Religious Activities and Religious Associations”. Scope of application: legislation and law enforcement. Conclusions: The result of the research work is an attempt to justify the need for adoption at this stage of development of relevant amendments aimed at improving legislation on religious activities and religious associations.